(untitled) (Eurasian Journal of Philology Science and Education, 2021)
As you know, orthology as an independent linguistic science is closely related to aspects of speech culture and linguistic norms. In improving the linguistic culture of society and achieving a high level of preservation of the basic linguistic norm in modern oral and written communication, orthological means, especially the spelling dictionary, are of particular importance. The spelling dictionary is an indicator of the diachronous-synchronous state of the language in particular, the evolution and development of society, in general. Therefore, in developed countries, a spelling dictionary with additions, changes is often released. At the current stage of the development of the Kazakh language, which is considered promising, aimed at changing the language situation, intensive work is being carried out to normalize, standardize and modernize the Kazakh language. The next edition of the Large Spelling Dictionary of the Kazakh Language is being prepared for release, in which the lexicographic principles are improved. The article discusses the basic lexicographic principles (selection of lexemes, supply of variant words, grammatical information, the use of graphemes, symbols, punctuation to clarify meanings, etc.), as well as in order to characterize the normalization and codification of individual lexical units, orthological analysis is carried out. Key words: spelling dictionary, principle of normativity, principle of frequency of use, principle of system description, main register, internal register, litter.